The Science of Occasion in the Books of Rhetoric, Criticism and Tafsir: The Concept and its Rooting - Abu Keshk, Zahera Tawfiq; Al-Obidy, Zahraa Tawfiq (Dirasat: Human and Social Sciences, 2023)
Objectives: This study aims at highlighting the rhetoric of the Science of Occasion among rhetoricians, critics, and Tafsir scholars. It also aims to unearth the mechanisms by which the text is constructed to suit the occasion in which it was articulated and demonstrate its performative rhetorical dimensions. In addition, the study intends to shed light on the efforts scholars have exerted to establish an independent and specialized science of occasion. Methods: The study depends on the inductive and analytical method to clarify the text and highlight its rhetorical aspects. It thus places the different viewpoints in conversation and presents the attitude that Muslim scholars have toward the Science of Occasion and the critical tools they employ to show the text’s unity and the extent to which the text echoes the occasion in which it was compiled or articulated. Results: The study stresses the strenuous efforts exerted by critics, rhetoricians and interpreters in exploring the text through its occasion. The study also stresses the fact that the Science of Occasion constitutes one of the Quranic sciences which strives to show the internal connections between verses and surahs according to the commendable Tafsir, highlighting the fact that this science has recently been evolving independently. Conclusions: The study recommends the necessity of paying attention to the importance of the efforts exerted by rhetoricians and critics in tracing the occasion concepts within the Quranic lesson and its connection to the Quran as one of the indispensable types of Tafsir.